2019
DOI: 10.1111/cen.14120
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic role of the lymphocyte‐to‐monocyte ratio for clinical outcomes of patients with progressive radioiodine‐refractory differentiated thyroid carcinoma treated by sorafenib

Abstract: Objectives:The lymphocyte-to-monocyte ratio (LMR) reflects the status of tumourinfiltrating immune cells and host immunity. The LMR has been reported as a prognostic marker in various cancers. The present study evaluated the role of the LMR as a prognostic marker in patients with progressive radioiodine-refractory (RAIR) differentiated thyroid carcinoma (DTC). Design: Retrospective cohort study.Patients: Forty patients with progressive RAIR DTC who were treated by sorafenib with available baseline complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A few studies showed that preoperative levels of NLR and PLR were associated with poorer survival and recurrence data of PTC (17,18). There were also some studies showing that PTC patients with a lower LMR had a poorer prognosis and a higher risk of recurrence (19)(20)(21). Besides, advanced tumor stage of PTC was found to be associated with a higher NLR and a lower LMR (22)(23)(24).…”
Section: Values Of the Sii-based Predictive Model On Predicting Clnmmentioning
confidence: 99%
“…A few studies showed that preoperative levels of NLR and PLR were associated with poorer survival and recurrence data of PTC (17,18). There were also some studies showing that PTC patients with a lower LMR had a poorer prognosis and a higher risk of recurrence (19)(20)(21). Besides, advanced tumor stage of PTC was found to be associated with a higher NLR and a lower LMR (22)(23)(24).…”
Section: Values Of the Sii-based Predictive Model On Predicting Clnmmentioning
confidence: 99%
“…A lower LMR has been correlated to advanced staged PTC ( 52 , 58 ). Low LMR was also associated with decreased overall and disease-free survival ( 58 ), including in patients with DTC refractory to radioiodine and treated with sorafenib ( 59 ), with LMR < 4 predicting shorter survival ( 58 , 59 ). A different study correlated a low LMR with recurrence, especially in patients with advanced PTC (stages II and III), with an optimal cut-off of 5 ( 61 ).…”
Section: Thyroid Tumorsmentioning
confidence: 99%
“…Song et al reported an association between lower LMR and larger tumors, multifocality and lymph node metastasis ( 58 ), other studies found no correlation between LMR and lymph node metastasis ( 52 , 61 ). More studies are needed to further assess the LMR usefulness in thyroid cancer, but LMR may be a promising tool in predicting recurrence and survival in patients with high-risk, advanced, or refractory PTC ( 58 , 59 , 61 ).…”
Section: Thyroid Tumorsmentioning
confidence: 99%
“…6) [58] and RAIR DTC patients treated with sorafenib (Fig. 7) [59]. A low LMR might be a reflection of both lymphopenia, which is a marker of weak immunity, and an elevated monocyte count in Copyright © 2020 Korean Endocrine Society the peripheral blood, which reflects elevated tumor-associated macrophage density in cancer tissue (corresponding to favorable conditions for tumor progression) [60].…”
Section: Understanding Of Tumor-host Interactions To Improve the Treatment Of Thyroid Cancermentioning
confidence: 99%